Pengembangan Multimedia Interaktif Model Games untuk Meningkatkan Respon Mahasiswa pada Mata Kuliah Organisasi dan Arsitektur Komputer - Pujawan, Kadek Agus Hendra (International Journal of Natural Science and Engineering, 2018)
The aims of this study were (1) to create an interactive multimedia by using games which is proper used by Politeknik Ganesha Guru students in computer organization and architecture course. (2) to know the feasibility level of interactive multimedia by using games according to content expert, media expert and learning design expert in computer organization and architecture course. (3) to know the students’ response to the development of interactive multimedia by using games in computer organization and architecture course. This study used Dick and Carey as the development model which invoved first semester students of Politeknik Ganesha Guru in Informatics Management Study Program. Based on the result of the data analysis from the content feasibility aspect made by the content expert indicated that the product is in accordance with the SAP of Computer Organization and Architecture courses. Tests conducted by media experts obtained a calculation result of 87% which is being in good qualification. Tests conducted by the design of learning experts obtained a calculation result of 88% which are in good qualification. The user/lecturer gave a good response. Field trials conducted got a result of 90% calculation which are in excellent qualification